Design, Synthesis, and Evaluation of Ribose-Modified Anilinopyrimidine Derivatives as EGFR Tyrosine Kinase Inhibitors - Hu, Xiuqin; Wang, Disha; Tong, Yi; Tong, Linjiang; Wang, Xia; Zhu, Lili; Xie, Hua; Li, Shiliang; Yang, You; Xu, Yufang (Frontiers in Chemistry, 2017)
The synthesis of a series of ribose-modified anilinopyrimidine derivatives was efficiently achieved by utilizing DBU or tBuOLi-promoted coupling of ribosyl alcohols with 2,4,5-trichloropyrimidine as key step. Preliminary biological evaluation of this type of compounds as new EGFR tyrosine kinase inhibitors for combating EGFR L858R/T790M mutant associated with drug resistance in the treatment of non-small cell lung cancer revealed that 3-N-acryloyl-5-O-anilinopyrimidine ribose derivative 1a possessed potent and specific inhibitory activity against EGFR L858R/T790M over WT EGFR. Based upon molecular docking studies of the binding mode between compound 1a and EGFR, the distance between the Michael receptor and the pyrimidine scaffold is considered as an important factor for the inhibitory potency and future design of selective EGFR tyrosine kinase inhibitors against EGFR L858R/T790M mutants.